Analysis of Fraud Hexagon Theory of Financial Fraudulent Reporting Using F-Score Model - Dini Wulandari; Syahril Ali (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
The research purpose is to determine and analyze the effect of fraud hexagon theory (stimulus, opportunity, rationalization, capability, ego dan collusion) to fraudulent financial reporting. The importance of this research is that fraudulent financial reporting can be detected as early as possible, so that the fraudulent fnancial reporting can be avoided and does not cause a loss for many parties. This research was conducted in the manufacture sector companies because it is a sector that is prone to fraudulent financial reporting. The sample in this research was selected using a purposive sampling technique which was obtained as many as 59 of manufacture sector companies listed on the Indonesia Stock Exchange in 2016-2020. The data analysis technique used SEM-PLS with WarpPLS 7.0 software. The result of this research show that stimulus, opportunity, rationalization and ego have positive and significant to fraudulent financial reporting, collusion have negative and significant to fraudulent financial reporting, while the capability did not have effect to fraudulent financial reporting.